Controllable modulation of coordination environments of Mn2+ in glasses and glass-ceramics for tunable luminescence. Issue 4 (April 2020) - Fang, Zaijin; Peng, Wencai; Zheng, Shupei; Qiu, Jianrong; Guan, Bai-Ou
Abstract: A phase-separated glass is designed to modulate the coordination environments of activators for achieving tunable luminescence in wide wavelength ranges. The luminescent properties and microstructures of Mn 2+ doped glasses are carefully investigated. It is found that the luminescence center of Mn 2+ is modulated to 620, 588 and 702 nm via the controllable precipitation of K2 SiF6, KZnF3 and ZnF2 crystals from the glass networks, respectively. The emissions of Mn 2+ -Mn 2+ dimers centered at 800 nm are also observed when Mn 2+ ions are confined in the fluoride crystal coordination environments. The phase-separated glass possesses great potential for providing diverse coordination environments for Mn 2+ and is beneficial for the formation of Mn 2+ -Mn 2+ dimers. This glass not only provides a highly promising development of optical gain material for tunable fiber lasers, but the modulation strategy based on phase-separated networks also offers excellent opportunities for manufacturing a wide range of photonic materials featuring multiple-wavelength luminescence.